Agnosticism: explorations in philosophy and religious thought - Fallon, Francis; Hyman, Gavin (Oxford University Press, 2020)
In a time marked by prominent public clashes between theists and atheists, much less attention has been given to the question of agnosticism, whether in public debate or in academic literature. This is all the more surprising given that so many in Western society feel unable to identify unequivocally with either theism or atheism. This book brings together some leading contemporary philosophers, from both the analytic and continental traditions, to give a sustained and in-depth treatment of the question of agnosticism. Approaching the question from a variety of stances and employing different methodologies, the contributors explore the various possible meanings of agnosticism today. Several of them develop what they describe as a 'New Agnosticism,' where the relationship with theism or forms of religious belief is not as mutually exclusive as has often been assumed. Others look for signs of agnosticism in places where it is not usually thought to be found, such as in forms of continental philosophy, and even in theology itself. They also raise interesting methodological questions at the intersection of analytic and continental philosophy. These are stimulating and innovative essays working with the most recent developments in philosophy and0religious thought. They open up new avenues of thought that will be of interest to philosophers, theologians, and other thoughtful readers, whether theist, atheist, or agnostic. -- Provided by publisher